A Qualitative Study of Factors Influencing Food Choices and Food Sources Among Adults Aged 50 Years and Older During the Coronavirus Disease 2019 Pandemic - Brady, Patrick J.; Askelson, Natoshia M.; Thompson, Helaina; Kersten, Sarah; Hopkins, Haley; Ashida, Sato; Nothwehr, Faryle; Janssen, Brandi; Frisvold, David (Journal of the Academy of Nutrition and Dietetics, 2023)
The coronavirus disease 2019 pandemic affected food availability and accessibility for many older adults, especially those experiencing food insecurity. Food citizenship is a theoretical framework that encourages the use of alternate over industrial food sources and can characterize where foods are acquired and how food choices are made. The purpose of this study is to explore how Iowans aged 50 years and older made choices about what foods to acquire and where to acquire foods during the coronavirus disease 2019 pandemic using food citizenship as a theoretical framework. We used in-depth interviews with Iowans aged 50 years and older (N = 60). We recruited respondents through Area Agencies on Aging, food banks, and food pantries. Individuals who contacted the research team, were aged 50 years and older, and spoke English were eligible. Half of the sample screened as food insecure. We conducted a thematic analysis to identify recurring themes. Food costs, personal preferences, and the healthfulness of food were cited as the most influential factors. Respondents said that the pandemic had not changed how they make choices, but increased prices had made costs more salient. Respondents primarily got their food from industrial food retailers, government programs, or food pantries. More than half of the respondents also acquired food from an alternate food source, such as a farmers’ market. Reasons for not using alternate food sources included cost and transportation barriers. It is essential to ensure that older adults have access to affordable, healthy foods, especially during crises such as the coronavirus disease 2019 pandemic. Alternate food sources provided supplementary, healthy food for many respondents, but there are opportunities to expand the use of these food sources. Incentivizing the use of alternate food sources through government programs and connecting the emergency food system to local producers could increase the consumption of healthy food.